Air pollution from motor vehicles : - Faiz, Asif (The World Bank, 1996)
This book consists of the following many parts such as emission standards and regulations, quantifying vehicle emissions, vehicle technology for controlling emissions, controlling emissions from in-use-vihicles, and fuel options for controlling emissions.